Surtitling today: new uses, attitudes and developments - Mateo, Marta (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Surtitling has exerted a noticeable twofold effect on the opera world, in which it originated: it has contributed substantially to increasing the number of opera goers, making opera more accessible and “audience-friendly” and changing audiences’ expectations towards their operatic experience, which has in turn affected the reception of works in the audience ’s native language; secondly, it has brought about innovations in opera production, introducing new languages and pieces in opera houses. Besides, surtitles have now been put to new uses, as some theatre productions have adopted them enabling drama to travel more extensively. This article will focus on the changes surtitling has produced in the contexts using it, the impact of technical advances on its own production and reception, as well as on its new consumers and uses.